SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-3896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ambient Temperatures on Exhaust Thermal Characteristics during Cold Start for Real World SI Car Urban Driving Tests

Abstract: Thermal characteristics of SI engine exhaust during cold start and warm up period were investigated for different ambient temperatures (-2 to 32 °C). A Euro 1 emission compliance SI car was tested using a real world urban driving cycle to represent typical city driving patterns and simulate ECE15 urban driving cycle. The test car was equipped with 27 thermocouples along the engine and exhaust pipes so as to measure metal and exhaust gas temperatures along the engine, exhaust and catalyst. The characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This evaluated the impact of a heat transfer much higher than discussed in the literature [58], [59] and is used to establish bounds on the performance of the controllers. Fig.…”
Section: Fuel and Emissions Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This evaluated the impact of a heat transfer much higher than discussed in the literature [58], [59] and is used to establish bounds on the performance of the controllers. Fig.…”
Section: Fuel and Emissions Resultsmentioning
confidence: 99%
“…The equation in (53) is algebraically manipulated to collect the term , resulting in the inequality (54) To create the linear program (LP), let (55) and let (56) Equations (55) and (56) define a row of linear constraints in the LP that correspond to a single state and action. Let be the th element of and define (57) and let (58) Equations (57) and (58) define a row of linear constraints in the LP that correspond to and an arbitrary state . Let be the th element of and define (59) and (60) Equations (59) and (60) define a row of linear constraints in the LP that correspond to the th element of the elements in and the th element of the elements in .…”
Section: ) Primal Lp Constructionmentioning
confidence: 99%
“…The study results in [20] showed that cold weather increases heat losses in the exhaust manifold and metal pipes and leads to greater heat losses in exhaust gases. As a result, 10.5 % of the fuel is lost because of heat losses and heat transfer by metal to the exhaust system.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, during cold start conditions, the engine, fuel, lubrication oil and the ambient temperature are very low and making fuel less volatile. It has been estimated that to reach warm up condition the lubrication oil takes about 10 minutes in summer and 14 minutes in winter and coolant water takes about 5 minutes in summer and 9 minutes in winter after cold start [5]. Thus, SI engine operations under cold conditions produces very high levels of emission than when operated under fully warmed up conditions.…”
Section: Background and Motivationmentioning
confidence: 99%
“…5 shows the 3D and sectional view of the computational grid of the heater part. From the section view the solid region was also considered for calculations…”
mentioning
confidence: 99%